Highly sensitive DNA sensors based on cerium oxide nanorods. (April 2018) - Nguyet, Nguyen Thi; Hai Yen, Le Thi; Van Thu, Vu; lan, Hoang; Trung, Tran; Vuong, Pham Hung; Tam, Phuong Dinh
Abstract: In this work, a CeO2 nanorod (NR)-based electrochemical DNA sensor was developed to identify Salmonella that causes food-borne infections. CeO2 NRs were synthesized without templates via a simple and unexpensive hydrothermal approach at 170 °C for 12 h by using CeO(NO3 )3 ·6H2 O as a Ce source. The DNA probe was immobilized onto the CeO2 NR-modified electrode through covalent attachment. The characteristics of the hybridized DNA were analyzed through electrochemical impedance spectroscopy (EIS) with [Fe(CN)6 ] 3−/4− as a redox probe. Experimental results showed that electron transfer resistance (Ret ) increased after the DNA probe was attached to the electrode surface and increased further after the DNA probe hybridized with its complementary sequence. A linear response of Ret to the target DNA concentration was found from 0.01 μM to 2 μM. The detection limit and sensitivity of the DNA sensor were 0.01 μM and 3362.1 Ω μM −1 cm −2, respectively. Various parameters, such as pH value, ionic strength, DNA probe concentration, and hybridization time, influencing DNA sensor responses were also investigated. Highlights: CeO2 NRs were synthesized without templates by using a facile hydrothermal approach. The biosensor detection mechanism is due to DNA hybridization leading to change of electron-transfer resistance. pH change should be strictly controlled during DNA detection. The detection limit and sensitivity of the DNA sensor are 0.01 μM and 3362.1 Ω μM −1 cm −2, respectively.